Research Features the Artificial Environment of Human Vital Activity - Usenko, Valerii; Zinenko, Tatyana; Zinenko, Alisa (International Journal of Engineering and Technology, 2018)
Questions about the methodological difference in engineering and humanitarian approaches to the architecture study are mentioned. Attention is focused on the relevance of studying the patterns of the structure of objects in an artificial environment. Unresolved problematic issues of investigating the invariants of the architectural systems structure are considered. The inherited qualities of architectural shaping are analyzed. It is noted that ways to improve the efficiency of the system, in particular architectural, rely on the use of a system approach in research.Â